2015
DOI: 10.4171/pm/1963
|View full text |Cite
|
Sign up to set email alerts
|

Solutions for linear conservation laws with gradient constraint

Abstract: We consider variational inequality solutions with prescribed gradient constraints for first order linear boundary value problems. For operators with coefficients only in L 2 , we show the existence and uniqueness of the solution by using a combination of parabolic regularization with a penalization in the nonlinear diffusion coefficient. We also prove the continuous dependence of the solution with respect to the data, as well as, in a coercive case, the asymptotic stabilization as time t → +∞ towards the stati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 23 publications
2
5
0
Order By: Relevance
“…x ∈ B r (y), for all y ∈ Σ . Similar results were obtained in [79] for the transported sandpile problem, for u(t) ∈ K k , such that…”
Section: Applicationssupporting
confidence: 83%
See 4 more Smart Citations
“…x ∈ B r (y), for all y ∈ Σ . Similar results were obtained in [79] for the transported sandpile problem, for u(t) ∈ K k , such that…”
Section: Applicationssupporting
confidence: 83%
“…⊓ ⊔ However, in this case, for the corresponding variational inequality, i.e. when G ≡ g(x,t), in [79] it was shown that the problem is well-posed and has similar stability properties, as in Section 3.1, with coefficients only in L 2 .…”
Section: The Scalar Quasi-variational Inequality With Gradient Constrmentioning
confidence: 94%
See 3 more Smart Citations